The Dependence of Water Consumption on the Pressure Conditions and Sensitivity Analysis of the Input Parameters - Tuhovčák, Ladislav; Sucháček, Tomáš; Ručka, Jan (MDPI, 2018)
The paper presents results and sensitivity analysis of the results of a real detailed study focused on changes in water consumption and its unevenness with changing pressure conditions in a particular observed office building. The dependence of water consumption on pressure is expressed using the FAVAD equation using the N3 coefficient. Parameters for sensitivity analysis are number of workers in the building, pulse value from water meter and length of time step for expressing unevenness of water consumption during the day.

The paper presents results and sensitivity analysis of the results of a real detailed study focused on changes in water consumption and its unevenness with changing pressure conditions in a particular observed office building. The dependence of water consumption on pressure is expressed using the FAVAD equation using the N3 coefficient. Parameters for sensitivity analysis are number of workers in the building, pulse value from water meter and length of time step for expressing unevenness of water consumption during the day.
The Dependence of Water Consumption on the Pressure Conditions and Sensitivity Analysis of the Input Parameters
Keywords: water consumption; pressure conditions; sensitivity analysis; input parameters; water consumption; pressure conditions; sensitivity analysis; input parameters